Психологические методы в работе с кадрами на АЭС - Абрамова В. Н. Владилена Николаевна; Белехов В. В. Валерий Владимирович; Бельская Е. Г. Екатерина Георгиевна; Колосова О. А. Ольга Алексеевна (Москва, Атомиздат, 1988)
Авторы указаны на обороте титульного листа